2022
DOI: 10.1093/pnasnexus/pgac029
|View full text |Cite
|
Sign up to set email alerts
|

Social mobility and biological aging among older adults in the United States

Abstract: Lower socioeconomic status is associated with faster biological aging, the gradual and progressive decline in system integrity that accumulates with advancing age. Efforts to promote upward social mobility may therefore extend healthy lifespan. However, recent studies suggest that upward mobility may also have biological costs related to the stresses of crossing social boundaries. We tested associations of life-course social mobility with biological aging using data from participants in the 2016 Health and Ret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(54 reference statements)
1
9
2
Order By: Relevance
“…For our first generation algorithm, our data do not accord with previous reports of the association of social mobility with age acceleration, that is we observe positive age acceleration association with upwards mobility, which is not in the same direction as previously reported 24 , 31 , 32 , where our data are statistically significant. This may be for a number of reasons: the analytic method we used which sought to separate mobility from origin and destination SEP 24 , 31 , 32 ; the measure of social position used in the analyses 32 and the measures of accelerated age used 32 . There is a wide body of literature on social mobility and broader measures of health; it is possible that the wider social mobility literature is mixed due to the failure to examine it independently of origin and destination SEP 36 , 37 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For our first generation algorithm, our data do not accord with previous reports of the association of social mobility with age acceleration, that is we observe positive age acceleration association with upwards mobility, which is not in the same direction as previously reported 24 , 31 , 32 , where our data are statistically significant. This may be for a number of reasons: the analytic method we used which sought to separate mobility from origin and destination SEP 24 , 31 , 32 ; the measure of social position used in the analyses 32 and the measures of accelerated age used 32 . There is a wide body of literature on social mobility and broader measures of health; it is possible that the wider social mobility literature is mixed due to the failure to examine it independently of origin and destination SEP 36 , 37 .…”
Section: Discussioncontrasting
confidence: 99%
“…The second generation measures were created to be predictive of mortality and are more reflective of biological age 35 . For our first generation algorithm, our data do not accord with previous reports of the association of social mobility with age acceleration, that is we observe positive age acceleration association with upwards mobility, which is not in the same direction as previously reported 24 , 31 , 32 , where our data are statistically significant. This may be for a number of reasons: the analytic method we used which sought to separate mobility from origin and destination SEP 24 , 31 , 32 ; the measure of social position used in the analyses 32 and the measures of accelerated age used 32 .…”
Section: Discussioncontrasting
confidence: 99%
“…The diminishing returns hypothesis, which has been validated in the literature, posits that African American adults do not experience the same health benefits of higher SES as White adults in the US. For example, the racial nonequivalence of SES-related health benefits has been documented for college completion, the risk of metabolic syndrome, the costs of social mobility, and biological aging . In fact, the SES gradient associated with biological aging is only partially due to health behaviors, again emphasizing that epigenetic aging is modulated by unmeasured stressful social conditions as well as genetic risk …”
Section: Discussionmentioning
confidence: 99%
“…For example, the racial nonequivalence of SES-related health benefits has been documented for college completion, the risk of metabolic syndrome, the costs of social mobility, and biological aging. 40,41 In fact, the SES gradient associated with biological aging is only partially due to health behaviors, again emphasizing that epigenetic aging is modulated by unmeasured stressful social conditions as well as genetic risk. 13 The results from previous HANDLS studies [42][43][44][45][46][47] that focused on poverty status were not completely concordant with the DunedinPACE data.…”
Section: Jama Network Open | Genetics and Genomicsmentioning
confidence: 99%
“…We recently showed that DunedinPACE is accelerated in individuals with low levels of education, and slowed in those with higher levels of education (15,16). In this study, we build on these observations to test the hypothesis that higher educational attainment promotes longevity by slowing the pace of aging.…”
Section: Introductionmentioning
confidence: 99%